Efektifitas Project Based Learning (PjBL) Sebagai Bentuk Implementasi Kurikulum Merdeka dalam Pembelajaran Matematika - Dwi Fani Eriza; Muhammad Sofian Hadi (Program Studi Pendidikan Matematika, 2023)
The learning crisis associated with the Co-19 pandemic emergency has had a major impact on changes in education in Indonesia. Applying the project-based learning (PjBL) model is an independent curriculum implementation by the Ministry of Education, Culture, Sports, Science and Technology (Kemdikbudristek) to emerge from the crisis and restore learning after the Co-19 pandemic. The purpose of this article is to discuss the effectiveness of the project-based learning model as an independent curriculum application for learning mathematics. It is a method of literature research or library research by filtering the most relevant sources on the topic to be studied or addressed, then drawing conclusions, noting various key points and implementing them later.form of writing. The results of implementing the PjBL model will have a positive impact on the development of students' mathematical learning skills and provide solutions for post-pandemic recovery